Groundwater dependent ecosystems in coastal Mediterranean regions: Characterization, challenges and management for their protection. (1st April 2020) - Erostate, M.; Huneau, F.; Garel, E.; Ghiotti, S.; Vystavna, Y.; Garrido, M.; Pasqualini, V.
Abstract: Coastal lagoons deliver a wide range of valuable ecosystem goods and services. These ecosystems, that are often maintained by direct or indirect groundwater supplies, are collectively known as groundwater dependent ecosystems (GDEs). The importance of groundwater supplies is greatly exacerbated in coastal Mediterranean regions where the lack of surface water and the over-development of anthropogenic activities critically threaten the sustainability of coastal GDEs and associated ecosystem services. Yet, coastal GDEs do not benefit from a legal or managerial recognition to take into account their specificity. Particular attention should be paid to the characterization of environmental and ecological water requirements. The hydrogeological knowledge about the management and behavior of coastal aquifers and GDEs must be strengthened. These investigations must be supplemented by a stronger assessment of potential contaminations to develop local land-uses and human activities according to the groundwater vulnerability. The quantitative management of water resources must also be better supervised and/or more constrained in order to ensure the water needs necessary to maintain coastal GDEs. The transdisciplinary approach between hydrogeology, hydrology, social sciences and law is essential to fully understand the socio-economic and environmental complexity of coastal GDEs. Priority must now be given to the development of an appropriate definition of coastal GDEs, based on a consensus between scientists and lawyers. It is a necessary first step to develop and implement specific protective legislation and to define an appropriate management scale. The investment and collaboration of local water users, stakeholders and decision-makers need to be strengthened through actions to favor exchanges and discussions. All water resources in the coastal areas should be managed collectively and strategically, in order to maximize use efficiency, reduce water use conflicts and avoid over-exploitation. It is important to continue to raise public awareness of coastal aquifers at the regional level and to integrate their specificities into coastal zone management strategies and plans. In the global context of unprecedented anthropogenic pressures, hydro-food crises and climate change, environmental protection and preservation of coastal GDEs represents a major challenge for the sustainable socio-economic and environmental development of Mediterranean coastal zones. Graphical abstract: Image 1 Highlights: Unprecedented synthesis on the management issues of Mediterranean coastal GDEs. Critical assessment of coastal GDEs' current status and management challenges. Transdisciplinary approach to highlight major dysfunctions in coastal GDEs management. Identification of important deficiencies in definition, legislation and management. Missing knowledge and involvement hinder the sustainable development of coastal areas.